2023
DOI: 10.7759/cureus.38380
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of ChatGPT as a Potential Substitute for Diabetes Educators

Abstract: This review article explores the potential of ChatGPT as a substitute for diabetes educators. Diabetes is a prevalent chronic disease that requires ongoing education and support for patients to effectively manage their condition. However, there is a shortage of diabetes educators, and traditional education methods have limitations in addressing patients' individual needs. ChatGPT is an artificial intelligence technology that offers a personalized and interactive approach to education and support. In this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Some research also supported this opinion. ChatGPT had the potential to be used as a diabetic educator [23]. It could also provide an effective diet plan for people with food allergies, albeit with minor errors [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some research also supported this opinion. ChatGPT had the potential to be used as a diabetic educator [23]. It could also provide an effective diet plan for people with food allergies, albeit with minor errors [13].…”
Section: Discussionmentioning
confidence: 99%
“…Those tasks represented a sample of proposed LLM uses that were synthesized from the literature and included, but were not limited to, optimizing alerts for clinical decision support, providing a differential diagnosis, writing a discharge summary, recommending treatment options, translating radiology reports into layperson language, writing scientific manuscripts, and generating personalized study plans for students or trainees among others. 2 6 7 8 15 16 17 18 19 20 21 22 23 24 25 …”
Section: Methodsmentioning
confidence: 99%
“…Artificial intelligence (AI) natural language processing chatbots such as ChatGPT are freely accessible to the general public. In clinical medicine, investigators have studied the role of ChatGPT in training medical students and in educating patients on diabetes mellitus, highlighting several key strengths but also raising potential pitfalls and risks with its use [1][2][3]. More recently, we showed that ChatGPT can play a complementary role to a traveller's health consultation in providing pre-travel advice [4].…”
Section: Introductionmentioning
confidence: 99%